Evaluation on Potential Contributions of Protease Activated Receptors Related Mediators in Allergic Inflammation - Huiyun Zhang; Xiaoning Zeng; Shaoheng He (Mediators of Inflammation, 2014)
Protease activated receptors (PARs) have been recognized as a distinctive four-member family of seven transmembrane G protein-coupled receptors (GPCRs) that can be cleaved by certain serine proteases. In recent years, there has been considerable interest in the role of PARs in allergic inflammation, the fundamental pathologic changes of allergy, but the potential roles of PARs in allergy remain obscure. Since many of these proteases are produced and actively involved in the pathologic process of inflammation including exudation of plasma components, inflammatory cell infiltration, and tissue damage and repair, PARs appear to make important contribution to allergy. The aim of the present review is to summarize the expression of PARs in inflammatory and structural cells, the influence of agonists or antagonists of PARs on cell behavior, and the involvement of PARs in allergic disorders, which will help us to better understand the roles of serine proteases and PARs in allergy.